Associations between RetNet gene polymorphisms and the efficacy of orthokeratology for myopia control: a retrospective clinical study - Xia, Ruijing; Yu, Xiangyi; Wu, Hao; Peng, Lulu; Du, Zhenlin; Yu, Xiaoguang; Xing, Shilai; Lu, Fan; Mao, Xinjie (Eye and vision (Novato, Calif.), 2025)
This study investigated how clinical and genetic factors impact the effectiveness of orthokeratology lenses in myopia. A retrospective clinical study was conducted with a sample of 545 children aged 8-12 years who had myopia and have initially worn orthokeratology lenses for one year. Whole-genome sequencing (WGS) was also performed on 60 participants in two groups, one with rapid axial length (AL) progression of larger than 0.33 mm and the other with slow AL progression of less than 0.09 mm. The RetNet database was used to screen candidate genes that may contribute to the effectiveness of orthokeratology lenses in controlling myopia. Children with greater baseline AL, greater spherical equivalent (SE) and greater age had better myopia control with orthokeratology lenses. A significant excess of nonsynonymous variants was observed among those with slow myopia progression, and these were prominently enriched in retinal disease-related genes. Subsequently, RIMS2 [odds ratio (OR) = 0.01, P = 0.0097] and LCA5 (OR = 9.27, P = 0.0089) were found to harbor an excess number of nonsynonymous variants in patients with slow progression of high myopia. Two intronic common variants rs36006402 in SLC7A14 and rs2285814 in CLUAP1 were strongly associated with AL growth. The identification of these novel genes associated with the effectiveness of orthokeratology lens therapy in myopic children provides insight into the genetic mechanism of orthokeratology treatment. The effectiveness of orthokeratology lens treatment relates to interindividual variability in the control of AL growth in myopic eyes. The efficacy increased when patients carried more nonsynonymous variants in retinal disease-related gene sets. These data serve as reference for genetic counselling and the management of patients who choose orthokeratology lenses to control myopia.